2004
DOI: 10.1161/01.cir.0000150639.98514.6c
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Venous Thromboembolism in Surgical Patients

Abstract: Abstract-Venous thromboembolism (VTE) is a common complication of surgical procedures. The risk for VTE in surgical patients is determined by the combination of individual predisposing factors and the specific type of surgery. Prophylaxis with mechanical and pharmacological methods has been shown to be effective and safe in most types of surgery and should be routinely implemented. For patients undergoing general, gynecologic, vascular, and major urologic surgery, low-dose unfractionated heparin or low-molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
163
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 78 publications
3
163
1
8
Order By: Relevance
“…Although VTE is relatively common in the general population, it is far more common during the post-operative period [25,27,[39][40][41][42][51][52][53]. Proposed explanations for this phenomenon include limited post-operative mobility, which can promote venous stasis, and damage to endothelial tissue, as discussed above.…”
Section: Vte In Brain Tumor Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although VTE is relatively common in the general population, it is far more common during the post-operative period [25,27,[39][40][41][42][51][52][53]. Proposed explanations for this phenomenon include limited post-operative mobility, which can promote venous stasis, and damage to endothelial tissue, as discussed above.…”
Section: Vte In Brain Tumor Patientsmentioning
confidence: 99%
“…Studies have shown that other risk factors for VTE include age, sex, ethnicity, blood type, length of hospital stay, operative duration, and coagulation status [3,6,[8][9][10]14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Standard prophylactic measures for VTE include chemical anticoagulation, mechanical prophylaxis, and increased ambulation during the post-operative period [36,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. This paper seeks to review the relevant and current literature on VTE in brain tumor patients, with particular focus on the risk factors and presenting symptoms of VTE, treatment options for those with VTE, and a review of current prophylactic measures for VTE.…”
Section: Introductionmentioning
confidence: 99%
“…There seems to be a lack of consensus on the use of pharmacological prophylaxis. Some authors suggest pharmacological prophylaxis to be safe (12,17) while there are reports that indicate the risk of hemorrhage is higher (1,6,7,14).…”
Section: Akmangit I Et Al: Vena Cava Filter Versus Low Molecular Weimentioning
confidence: 99%
“…Given the possibility of a surgical intervention, it is questionable to use an antiaggregant and anticoagulant agent for DVT and PE prophylaxis due to high risk of bleeding. Pharmacological agents might result in catastrophic complications in the peri-and postoperative period and their use is therefore not considered to be beneficial (1,6,7,23,18,19). Although absolute and relative indications of vena cava filters are still debatable, their prophylactic use in patients with neurosurgical problems has not been reported thoroughly in the literature (8,10,20,22,24,26,28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation